Marketing Communication Strategy in Increasing the Number of Advertisements: A Case Study of RRI Medan - Siregar, Suci Afria Sasty; Lubis, Fauzi Arif; Harahap, Muhammad Ikhsan (Graduate Program Magister Manajemen Pendidikan, 2024)
The purpose of this research is to delve deeper into how marketing communication strategies can increase the number of advertisements, using RRI Medan as a case study. This study employs a qualitative descriptive research method to allow the researcher to provide a deeper and more comprehensive explanation of the case in the field. The determination of informants in the study uses source triangulation, where data sources are sampled based on certain considerations. The results of the study show that the strategies employed by RRI Medan include marketing strategy analysis and market target processes, which consist of market opportunity analysis and competitive analysis by implementing advertising, direct marketing, sales promotion, and public relations. This article contributes to everyone works in marketing or business, that market opportunity analysis and competitive analysis by implementing advertising, direct marketing, sales promotion, and public relations is effective and optimal for marketing strategy.